PSI Photoinhibition and Changing CO2 Levels Initiate Retrograde Signals to Modify Nuclear Gene Expression - Kılıç Mehmet; Käpylä Ville; Gollan Peter J; Aro Eva-Mari; Rintamäki Eevi (MDPI, 2025)
Photosystem I (PSI) is a critical component of the photosynthetic machinery in plants. Under conditions of environmental stress, PSI becomes photoinhibited, leading to a redox imbalance in the chloroplast. PSI photoinhibition is caused by an increase in electron pressure within PSI, which damages the iron–sulfur clusters. In this study, we investigated the susceptibility of PSI to photoinhibition in plants at different concentrations of CO2, followed by global gene expression analyses of the differentially treated plants. PSI photoinhibition was induced using a specific illumination protocol that inhibited PSI with minimal effects on PSII. Unexpectedly, the varying CO2 levels combined with the PSI-PI treatment neither increased nor decreased the likelihood of PSI photodamage. All PSI photoinhibition treatments, independent of CO2 levels, upregulated genes generally involved in plant responses to excess iron and downregulated genes involved in iron deficiency. PSI photoinhibition also induced genes encoding photosynthetic proteins that act as electron acceptors from PSI. We propose that PSI photoinhibition causes a release of iron from damaged iron–sulfur clusters, which initiates a retrograde signal from the chloroplast to the nucleus to modify gene expression. In addition, the deprivation of CO2 from the air initiated a signal that induced flavonoid biosynthesis genes, probably via jasmonate production.